2019
DOI: 10.4258/hir.2019.25.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Health on Obese Adults: A Systematic Review and Meta-Analysis

Abstract: ObjectivesThis study was conducted to examine the effects of mobile health (mHealth), using mobile phones as an intervention for weight loss in obese adults.MethodsAn electronic search was carried out using multiple databases. A meta-analysis of selected studies was performed. The effects of mHealth were analyzed using changes in body weight and body mass index (BMI).ResultsWe identified 20 randomized controlled trials (RCTs) involving 2,318 participants who fit our inclusion criteria. The meta-analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 14 publications
5
45
0
1
Order By: Relevance
“…Weight loss effects reported here are comparable in magnitude to other reviews that include a SMS within multicomponent mHealth interventions . For example, a systematic review examining mobile health interventions including SMS for adults with obesity reported a weight effect of −2.35 kg (95% CI, −2.84 to −1.87 kg), similar to −2.28 kg (95% CI −3.17, − 1.39 kg) found in the current review.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Weight loss effects reported here are comparable in magnitude to other reviews that include a SMS within multicomponent mHealth interventions . For example, a systematic review examining mobile health interventions including SMS for adults with obesity reported a weight effect of −2.35 kg (95% CI, −2.84 to −1.87 kg), similar to −2.28 kg (95% CI −3.17, − 1.39 kg) found in the current review.…”
Section: Discussionsupporting
confidence: 83%
“…This review did not find differences in weight loss effects on the basis of intervention duration, SMS‐frequency, use of theory, SMS interactivity, and SMS tailoring. A previous systematic review of mobile health interventions found highest weight loss effects at 6 months with a reduction in effects sizes at 12 months, which remained statistically significant . The current review found a similar pattern of effects sizes, typical for weight loss results over time .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results showed significant reductions in body weight, BMI and WC, which was in line with the suggested significant benefits of eHealth interventions in regard to body weight, BMI and WC in the two studies. 38 39 Weight loss is the cornerstone of MetS management. 40 Weight loss has beneficial impacts on MetS.…”
Section: Discussionmentioning
confidence: 99%